Lithium Niobate Phononic Crystals for Tailoring Performance of RF Laterally Vibrating Devices - Ruochen Lu; Manzaneque, Tomas; Yansong Yang; Songbin Gong (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2018)
This paper reports the first demonstration of phononic crystals (PnCs) in suspended lithium niobate thin films, which exhibit band gaps for tailoring the performance of laterally vibrating devices. Transmission and reflection properties of lithium niobate PnCs for both shear-horizontal (SH0) and length-extensional (S0) modes have been investigated and subsequently explored in two applications. In the first case, PnC-embedded delay lines were designed for filtering with stopbands, while in the second case, PnC-bounded resonators were implemented for spurious mode suppression. Equivalent circuit models incorporating acoustic scattering parameters of the designed PnCs and Mason's model of the transducers have been built for each application. Benchmarked to reference devices without PnCs, the measured PnCs embedded in delay lines show 20-dB attenuation in the stopbands and less than 2-dB loss in the passbands for the SH0 mode, and 30-dB attenuation in the stopbands and less than 10-dB loss in the passbands for the S0 mode. The fabricated piezoelectric PnC-bounded resonator has shown a quality factor of 434 at 142.7 MHz with undesired spurious modes significantly suppressed. These demonstrations show that lithium niobate PnCs for laterally vibrating devices can potentially lead to wideband and low-loss acoustic functions for radio frequency signal processing.